On Researching Shame in the Church - Nash, Sally (Practical theology, 2017)
This article explores the way in which undertaking research on shame in the church as part of my ordination training has engendered transformative learning impacting both my professional and personal life. The origin of my interest in shame was an incident at primary school and the article begins with a short autoethnographic account of this event. The research is described in relation to the following processes: clarifying the concept of shame; autoethnography, vulnerability, practical theology, conscientization, pedagogy, catharsis, healing, liturgy and ecclesial. Phenomenological definitions of shame, institutional shame and practical theology as developed in the thesis are included.